Nioella nitratireducens gen. nov., sp nov., a novel member of the family Rhodobacteraceae isolated from Azorean Island - Rajasabapathy, Raju; Mohandass, Chellandi; Yoon, Jung-Hoon; Dastager, Syed Gulam; Liu, Qing; Khieu, Thi-Nhan; Son, Chu Ky; Li, Wen-Jun; Colaco, Ana (Antonie Van Leeuwenhoek International Journal of General and Molecular Microbiology, 2015)
A novel Gram-negative, non-spore forming, rod-shaped aerobic bacterium, designated SSW136(T), was isolated from a surface seawater sample collected at Espalamaca (in Faial Island), Azores. Growth was found to occur from 10 to 37 A degrees C, pH 6.0-8.0, and with 2-11 % of NaCl. 16S rRNA gene sequence indicated that the strain SSW136(T) belongs to the family Rhodobacteraceae. Strain SSW136(T) exhibited 96.3, 95.9, 95.7 and 95.5 sequence similarity to the type strains Oceanicola litoreus M-M22(T), Roseovarius aestuarii SMK-122(T), Marivita geojedonensis DPG-138(T), and Pseudoruegeria aquimaris SW-255(T) respectively. Neighbour-joining and maximum-parsimony phylogenetic trees based on 16S rRNA gene sequences revealed that strain SSW136(T) was affiliated to the family Rhodobacteraceae and formed a separate branch. The G+C content was 63.5 mol%. The major respiratory quinone was found to be Q-10. The polar lipids of strain SSW136(T) consisted of phosphatidylcholine, phosphatidylethanolamine, phosphatidylglycerol, two unidentified aminolipids and three unidentified phospholipids. The major fatty acids were C-18:1 omega 7c (46.5 %), Cyclo-C-19:0 omega 8c (16.0 %) and C-16:0 (12.8 %). On the basis of the morphological, genotypic, chemotaxonomic characteristics and low DNA-DNA relatedness, strain SSW136(T) is proposed to represent a novel genus and novel species, Nioella nitratireducens gen. nov., sp. nov., in the family Rhodobacteraceae. The type strain is SSW136(T) (=KCTC 32417(T) = NCIM 5499(T)).
Keywords: Espalamaca; Nioella nitratireducens; Novel genus and species; Polyphasic taxonomy; Seawater

Vitellibacter nionensis sp nov., isolated from a shallow water hydrothermal vent - Rajasabapathy, Raju; Mohandass, Chellandi; Yoon, Jung-Hoon; Dastager, Syed Gulam; Liu, Qing; Thi-Nhan Khieu; Chu Ky Son; Li, Wen-Jun; Colaco, Ana (International Journal of Systematic and Evolutionary Microbiology, 2015)
A novel, Gram-stain-negative, non-motile, rod-shaped yellow bacterium, designated VBW088(T) was isolated from a shallow water hydrothermal vent in Espalamaca in the Azores. Phylogenetic analysis based on 16S rRNA gene sequences showed that strain VBW088(T) clustered with three type strains of species of the genus Vitellibacter and exhibited a sequence similarity of 97.3% with Vitellibacter soesokkakensis RSSK-12(T). However, strain VBW088(T) and V. soesokkakensis RSSK-12(T) exhibited low DNA-DNA relatedness (12.7 +/- 3.5 %). Strain VBW088(T) was positive for catalase and oxidase. Growth occurred at 10-37 degrees C, with the optimum at 80 degrees C, and at pH 6.0-8.0 (optimum pH 6.0) and in up to 5% (w/v) NaCl with optimum growth at 1-2% (w/v) NaCl. The major fatty acids (>10%) were iso-C-15:0 (33.5%) and iso-C-17:0 3-OH (32.0%). The polar lipids detected in strain VBW088(T) consisted of phosphatidylethanolamine, one unidentified aminolipid and three unidentified phospholipids. The DNA G+C content of strain VBW088(T) was 36.7 mol%. On the basis of phylogenetic inference, DNA-DNA relatedness, chemotaxonomic analysis and physiological data, the isolate represents a novel species of the genus Vitellibacter, for which the name Vitellibacter nionensis sp. nov. is proposed, with the type strain as VBW088(T). (=KCTC 32420(T)=MCC 2354(T)).